The experiences of help-seeking in people with obsessive compulsive disorder: an internet survey. (12th August 2016) - Vuong, Thanh Mai; Gellatly, Judith; Lovell, Karina; Bee, Penny
Abstract: Obsessive compulsive disorder (OCD) is a debilitating mental health disorder, with prevalence in adults of around 3.1%. The social and economic consequences of OCD are high for patients and their families. It is unlikely to improve without treatment. Help-seeking for treatment is often delayed and studies have found an average treatment gap of up to 17 years. This study aimed to explore the factors that influenced how, when and why people sought help and to identify any issues that they faced during help-seeking. Individuals experiencing OCD were invited to complete a web-based survey hosted on a national OCD charity website over a 3-month period. Eighty-eight individuals took part. Most had sought help from their general practitioner (GP), while others accessed websites and private services. Lack of awareness and understanding by health professionals was reported as a problem, as was the speed of referral or getting the right treatment. There is a need for further training and education for health professionals and GPs. Education and awareness campaigns for the general public, with more focus on how help can be sought, and on the different types of OCD may contribute to improving recognition of symptoms and accessing timely help.